2022
DOI: 10.3390/v14050860
|View full text |Cite
|
Sign up to set email alerts
|

Virome of Three Termite Species from Southern Vietnam

Abstract: Modern metagenomic approaches enable the effective discovery of novel viruses in previously unexplored organisms. Termites are significant ecosystem converters and influencers. As with the majority of tropical forest insects, termites are studied insufficiently, and termite virome remains especially understudied. Here, we studied the virome of lichenophagous and mycophagous termites (Hospitalitermes bicolor, Macrotermes carbonarius and Odontotermes wallonensis) collected in the Cat Tien National Park (Vietnam)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…1). The LsDV identified in this study shared the closest phylogenetic relationship with a virus identified from Macrotermes carbonarius in southern Vietnam (17_N1 + N237) [ 81 ]. M. carbonarius is an open-air foraging species that collects plant litter and wood debris to cultivate fungi in fungal gardens [ 82 ], termites may act as vectors, transmitting deltaflexivirus to other fungi.…”
Section: Discussionmentioning
confidence: 93%
“…1). The LsDV identified in this study shared the closest phylogenetic relationship with a virus identified from Macrotermes carbonarius in southern Vietnam (17_N1 + N237) [ 81 ]. M. carbonarius is an open-air foraging species that collects plant litter and wood debris to cultivate fungi in fungal gardens [ 82 ], termites may act as vectors, transmitting deltaflexivirus to other fungi.…”
Section: Discussionmentioning
confidence: 93%
“…Early studies have focused on the cockroach-specific densovirus for development as a biological control agent [18][19][20][21]. Advanced next-generation sequencing technologies and bioinformatic tools have enabled the identification and genetic characterization of novel viruses in several termites and cockroaches [15,[22][23][24]. These findings have important significance in reflecting viral origin, evolution and distribution in Blattodea.…”
Section: Introductionmentioning
confidence: 99%